A Study on Optoelectronic Properties of Copper Zinc Tin Sulfur Selenide: A Promising Thin‐Film Material for Next Generation Solar Technology. Issue 7 (26th May 2021) - Ali, Nisar; Zubair, M.; Khesro, Amir; Ahmed, Rashid; Uddin, Sarir; Shahzad, Naeem; Alrobei, Hussein; Kalam, Abul; Al‐Sehemi, Abdullah G.; Ul Haq, Bakhtiar
Abstract: Studies on copper zinc tin sulpher selenide (CZTSSe) thin‐film material and its applications as a base material are intensively being researched since it is an earth‐abundant, inexpensive, flexible, and interesting material for next‐generation optoelectronic technologies. Apropos, this study explores and reports the synthesis of CZTSSe thin films and their key optoelectronics characteristics. The reported films are fabricated on a soda‐lime glass substrate by using a physical vapor deposition technique, and then annealed from 250 to 450 °C. From the X‐ray diffraction analysis, the structure of the as‐deposited thin films is found to be amorphous in nature. Annealed thin films of CZTSSe exhibit polycrystalline nature with an average crystallite size of 46.3 nm in tetragonal structure. To determine the bandgap energy, as well as optical properties, the visible spectrophotometer, and four‐probe techniques, are used. From the measurements, the bandgap energy of the annealed film is found to be 1.64 eV at 450 °C which is in the optimal range as an absorber layer for solar cell devices. Similarly, by employing the four‐probe technique, I – V characteristics for the as‐deposited thin films, the material shows non‐ohmic behavior whereas the annealed film demonstrates partially ohmic with a resistance of 670 ohms. Abstract : Copper zinc tin sulfur selenide (CZTSSe) is an emerging absorbing material of solar cell. The annealed CZTSSe thin films exist in polycrystalline nature with an optimum bandgap of 1.64 eV and high‐absorption coefficient in the UV–vis range. The I – V behavior of the annealed films possesses ohmic nature with a low resistance of 670 ohms.